Hypersensitivity in Dentistry - Shelly Lelyana (Maranatha Christian University, 2020)
Immune system is a part of body defense system towards diseases, but the immune mechanism that normally defend the body could react in reverse or in other word could destroy its own body. This reaction is well known as hypersensitivity reaction. In dental practice, practitioners are using a few materials and several drugs to treat their patient, like metals, acrylics, antibiotics, hypnotics, anesthetics, to name a few. When using all sorts of dental materials and medication, dental practitioner should have known on how to handle the reaction that can possible happen, most importantly in worst case scenario like patient hypersensitivity reaction towards the materials or medication. These hypersensitivity reaction usually generate manifestations on the body and as a dental practitioner it is important to have an awareness on the signs and symptoms in the oral cavity, so practitioner could figure out on what the cause and how to treat it. Dental practitioners should be aware on the materials and drugs that could potentially be allergen towards patient and themselves. The aim of this literature review is to give information on some of the most common hypersensitivity reaction in dentistry.